Cytogenetics Classical and Molecular Strategies for Analysing Heredity Material - Larramendy, Marcelo L.; Soloneski, Sonia (IntechOpen, 2021)
This edited book, Cytogenetics - Classical and Molecular Strategies for Analysing Heredity Material, presents recent advances in the field of cytogenetics, paying special attention to methodological achievements developed worldwide that have driven the field forward. The contributors clearly discuss several concepts and approaches useful for understanding chromosomal structure and function at its various levels, highlighting chromosomes as visible carriers of heredity material.